Evaluation of Leukemia and Solid Tumors in Refugee Children in Turkey: A Tertiary Center Experience - Ayça Koca Yozgat; Derya Özyörük; Suna Emir; Ahmet Demir; Arzu Yazal Erdem; Can Barış Aker; Zeliha Güzelküçük; İnci Yaman Bajin; Dilek Kaçar; Neşe Yaralı; Namık Yaşar Özbek (Galenos Publishing House, 2023)
Cancer care is progressively became as a significant worldwide challenge. Wars can cause destructions and delays in cancer diagnosis and treatment of displaced people. Cancer cure rates need to be improved in indefensible populations such as refugees. In this study, we purposed to highlight the clinical peculiarities and outcomes of refugee children with cancer in our hospital. Our purpose was to present our findings and contribute to improve the health care for these children. Seventy one refugee pediatric patients admitted to the oncology and hematology units of our hospital between April 2011 and January 2019 were included in this study. The demographic characteristics of the patients at the initial diagnosis, their countries of origin, living conditions, histopathological diagnoses, treatments, relapse, and mortality data were analyzed retrospectively from the patient files. The median age of patients was 6.5±4.5 years, and the male-to-female ratio was 39/32. While 44 patients (61.9%) presented with complaints and had primary diagnoses in our hospital, the remaining 27 patients (38.1%) were diagnosed in their country and applied to our hospital for treatment. Our mean follow-up period was 18.2±18.8 months (1-90 months). As a result, 44 patients (62%) were alive and 22 (31%) were dead. The survival rate without relapse in the second year was 83.6%. Two and fiveyear survival rates were 77.5% vs. 58.1% respectively. Compared to Turkish children, lower survival rates were found in refugee children. In addition to cancer-specific factors such as tumor type and stage, some problems such as shelter, communication, adherence to treatment, and difficulties supplying medicine may be responsible for lower survival rates in refugee children. Further studies are needed to improve the survival rates of patients.